Can litter addition mediate plant productivity responses to increased precipitation and nitrogen deposition in a typical steppe?. Issue 4 (21st May 2016) - Shen, Yue; Chen, Wenqing; Yang, Gaowen; Yang, Xin; Liu, Nan; Sun, Xiao; Chen, Jishan; Zhang, Yingjun
Abstract: Plant litter is a key component of grassland and plays a major role in terrestrial ecosystem processes. Global climate change has been shown to considerably alter litter inputs to soils, which may feed back to the grassland ecosystem responses to climate change. In order to explore whether litter addition could mediate above and belowground productivity responses to short‐term increases in growing‐season precipitation and nitrogen deposition, we conducted a two‐year study on water, nitrogen and litter addition in Inner Mongolia grassland. After two years of treatments, our results showed that water, nitrogen, and litter addition increased aboveground biomass (AB) and belowground net primary productivity (BNPP). Besides, litter addition increased BNPP responses to water addition. These litter addition effects could be attributed to the influence of litter on soil moisture and soil nitrogen availability, ultimately increasing belowground water use efficiency (WUEBNPP ) and plant nitrogen uptake (NUPBNPP ). However, litter addition suppressed the aboveground biomass (AB) responses to nitrogen addition under ambient precipitation conditions by affecting soil moisture. In conclusion, our results suggest that ecosystem responses to short‐term increases in growing‐season precipitation and nitrogen deposition could be mediated by the increased litter input caused by climate change.